Evidence-based policy: framework, results and analysis from the New Zealand biotechnology sector. (16th March 2006) - Marsh, Dan
The New Zealand government has identified biotechnology as being a potential growth area worthy of special attention and government effort. This paper starts by describing the public policy initiatives by which the government aims to stimulate entrepreneurial activity and growth in the biotechnology sector. A framework for analysing the determinants of innovation is then described based on a synthesis of theoretical and empirical knowledge from various strands of the innovation literature. A series of hypotheses emerging from the framework are then tested using national survey data. Empirical results are then used to assess the extent to which government policy initiatives are supported by empirical evidence. Key findings focus on policies aimed at strengthening biotechnology capability, building on areas of strength and supporting collaboration, clustering and links.